A solution provider perspective: experiencing the COVID-19 global pandemic and the future of electronic monitoring - Desir, Katie (The journal of offender monitoring, 2021)
The pandemic was unpredictable and unequal in its effects. For companies in the EM field like Securus Monitoring, the disruptions and challenges led to improvements that will outlast the temporary conditions they were designed to address. The extent and way electronic monitoring is used may also have been transformed. This article explores the pandemic experience of Securus, including how internal operations were adapted to evolving health and safety concerns, the acceleration of video conferencing, how manufacturing ouput was sustained, permanent improvements to training procedures that grew out of pandemic-inspired changes, and how applications of EM in the marketplace have also changed and evolved.